One-pot Synthesis of Hexahydroquinazolinone using Co-Al2O3-SO3H as an Efficient Catalyst - Mehrabi, Masoumeh; Farhadi, Asadollah; Hasanzadeh, Neda; Kiasat, Ali Reza (Letters in Organic Chemistry, 2025)
By employing a catalytic proportion of Co-Al2O3-SO3H in a three-component Biginelli-type condensation, combining various aromatic aldehydes, 1,3-cyclohexadione, and urea, practical one-pot synthesis of hexahydroquinazolinone was accomplished. This method yielded hexahydroquinazolinones in good yields, which were further enhanced under reflux conditions. This approach offers several significant advantages, including high efficiency, straightforward reaction conditions, simple workup, reusable catalysts, superior yields, and shorter reaction times. The structure of the produced heterogeneous catalyst Co-Al2O3-SO3H was analyzed using Brunauer-Emmett-Teller (BET) analysis, X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM).
Keywords: heterogeneous catalyst